2010
DOI: 10.4049/jimmunol.0901188
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of NF-κB (RANK) Ligand Induces Ectodomain Shedding of RANK in Murine RAW264.7 Macrophages

Abstract: Osteoclastogenesis is a highly sophisticated process that involves a variety of membrane-bound proteins expressed in osteoblasts and osteoclast precursors. Over the past several years, proteolytic cleavage and release of the ectodomain of membrane-bound proteins, also referred to as ectodomain shedding, has emerged as an important posttranslational regulatory mechanism for modifying the function of cell surface proteins. In line with this notion, several membrane-bound molecules involved in osteoclastogenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…On the contrary, we found no skeletal defects in Egfr flox/flox /LysM-cre mice (Fig. 4F) or in Tace flox/flox /LysM-cre mice [17], [30] (data not shown), suggesting that the EGFR ligands released from cartilage cells in the growth plate act in an autocrine or paracrine manner and not as a chemoattractant for osteoclasts and their precursors. Furthermore, X-ray analysis revealed that the long bones of mutant mice that specifically lack EGFR in the chondrocytes are shorter than those of their wild-type littermates at 8 weeks of age (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…On the contrary, we found no skeletal defects in Egfr flox/flox /LysM-cre mice (Fig. 4F) or in Tace flox/flox /LysM-cre mice [17], [30] (data not shown), suggesting that the EGFR ligands released from cartilage cells in the growth plate act in an autocrine or paracrine manner and not as a chemoattractant for osteoclasts and their precursors. Furthermore, X-ray analysis revealed that the long bones of mutant mice that specifically lack EGFR in the chondrocytes are shorter than those of their wild-type littermates at 8 weeks of age (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…TNFα converting enzyme (TACE; ADAM-17) is one such enzyme and generates the soluble forms of TNFα as well as RANKL [59,80]. Inhibition of TACE activity upregulates surface RANK expression on monocytes [81], and, most recently, RANKL was shown to upregulate TACE-mediated shedding of the RANK ectodomain in a TRAF6-dependent manner indicating a negative feedback mechanism to regulate RANK surface expression [82]. Therefore, these observations strongly suggest that activation or inhibition of TACE could indeed play a significant role in the regulation of RANK signalling.…”
Section: The Rank Signalling Pathwaymentioning
confidence: 99%
“…Therefore, the patient phenotype seen as a result of harbouring such truncating mutations is likely the combined functional effect of the expression of the truncated protein together with that of reduced levels of RANK expression. The effect of the mutation A244S in the cytoplasmic domain of RANK is not clear as deletion of this region does not affect osteoclast formation [82], and the patient carrying this mutation was a compound heterozygote carrying C175R on the other allele complicating the functional analysis.…”
Section: Loss-of-function Mutations In Rankmentioning
confidence: 99%
“…ADAM17 has recently been shown to cleave the RANK receptor in macrophages [51]. RANK signaling is a key signaling pathway in the development of mature medullary Aire-expressing TECs at the fetal stage [52], [53], [54].…”
Section: Discussionmentioning
confidence: 99%